2015
DOI: 10.5551/jat.30007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pioglitazone for Secondary Stroke Prevention in Patients with Impaired Glucose Tolerance and Newly Diagnosed Diabetes: The J-SPIRIT Study

Abstract: Aim:Prediabetes is an independent risk factor for future stroke. However, no effective treatment has yet been established for the recurrence of stroke in patients with prediabetes. Here we investigated the effects of pioglitazone, a potent peroxisome proliferator-activated receptor-gamma agonist, for the reduction of recurrent stroke in patients with prediabetes. Methods: Participants were patients who had a symptomatic ischemic stroke or transient ischemic attack (TIA) without a history of type 2 diabetes mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 33 publications
2
46
0
1
Order By: Relevance
“…The studies included participants with or without prior cardiovascular diseases. Two studies (IRIS, J-SPIRIT)9 10 enrolled only participants with a stroke or transient ischaemic attack, while in the other studies the majority of participants had not experienced a stroke or transient ischaemic attack at the time of study entry. The number of participants ranged from 121 to 5238.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies included participants with or without prior cardiovascular diseases. Two studies (IRIS, J-SPIRIT)9 10 enrolled only participants with a stroke or transient ischaemic attack, while in the other studies the majority of participants had not experienced a stroke or transient ischaemic attack at the time of study entry. The number of participants ranged from 121 to 5238.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, several randomised controlled trials have been published to evaluate the effect of pioglitazone on occurrence of cardiovascular events in various types of patients 8–14. These trials comprised patients with insulin resistance,9 pre-diabetes (eg, impaired fasting glucose and/or impaired glucose tolerance)8 10 or type 2 diabetes mellitus.…”
Section: Manuscriptmentioning
confidence: 99%
“…Our final analysis included 3 randomized controlled trials that enrolled 4980 individuals, with 2488 participants (50%) randomly assigned to the pioglitazone group and 2492 participants (50%) to the control group (Figure 1). 16,19,20 The study design and patient baseline characteristics of these randomized controlled trials are shown in Table 1. Analyzed data were abstracted from whole trials that enrolled only stroke or TIA patients (2 trials) 16,19 and a separately reported subgroup of stroke patients (1 trial).…”
Section: Resultsmentioning
confidence: 99%
“…20,21 One trial included patients with insulin resistance and having their fasting glucose <126 mg/dL and hemoglobin A 1c <7%, 16 another trial included patients with impaired glucose tolerance or newly diagnosed diabetes mellitus, 19 and a third trial included patients with diabetes mellitus. 20 The number of participants ranged from 120 19 to 3876. 16 The median study duration was 4.4 years (ranged from 2.8 19 to 4.8 years 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation